2015
DOI: 10.1093/nar/gkv645
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and post-transcriptional control of adipocyte differentiation by Jumonji domain-containing protein 6

Abstract: Jumonji domain-containing protein 6 (JMJD6) is a nuclear protein involved in histone modification, transcription and RNA processing. Although JMJD6 is crucial for tissue development, the link between its molecular functions and its roles in any given differentiation process is unknown. We report that JMJD6 is required for adipogenic gene expression and differentiation in a manner independent of Jumonji C domain catalytic activity. JMJD6 knockdown led to a reduction of C/EBPβ and C/EBPδ protein expression witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 66 publications
4
39
0
Order By: Relevance
“…In line with other studies where the JMJD6 molecular interactions and not its enzymatic activity mediate the protein function (26,27), our data reveal new biologic properties of JMJD6 and of JMJD6-derived peptides apparently independent of JmjC-domain activity. However, the peculiar characteristics of P4E11 mAb in recognizing a conformational target epitope, which also includes amino acid sequences of the JmjC domain, do not exclude the notion that in vivo, a wide range of activities might be modulated by the antibody, including the JMJD6 enzymatic activity itself.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with other studies where the JMJD6 molecular interactions and not its enzymatic activity mediate the protein function (26,27), our data reveal new biologic properties of JMJD6 and of JMJD6-derived peptides apparently independent of JmjC-domain activity. However, the peculiar characteristics of P4E11 mAb in recognizing a conformational target epitope, which also includes amino acid sequences of the JmjC domain, do not exclude the notion that in vivo, a wide range of activities might be modulated by the antibody, including the JMJD6 enzymatic activity itself.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, JMJD6 overexpression in breast cancers is associated with poor prognosis (24), and its ectopic expression increases cancer cell line proliferation while its silencing reduces cell growth, motility, and invasion (24,25). Through alternative nonenzymatic activities, JMJD6 modulates RNA splicing by interacting with the arginine-serine (RS) domains of SR and SR-like proteins (26) and controls adipocyte differentiation through transcriptional and post-transcriptional mechanisms (27).…”
mentioning
confidence: 99%
“…RNA-binding motif protein 4 (RBM4) has also been reported to regulate the splicing of adipocyte-specific genes, including the insulin receptor, PPARγ, and PREF-1, thereby facilitating brown adipocyte development (54). Whether other aspects of posttranscriptional RNA processing, such as mRNA export from the nucleus, mRNA turnover, and translation initiation, are also regulated during adipogenesis has heretofore been unclear (55)(56)(57). Furthermore, the importance of RNA processing factors for the development and function of adipose tissue in vivo has not been tested.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its function in transcriptional control, we and others have shown that JMJD6 also interacts with multiple splicing factors, and is involved in gene splicing control (Heim et al, 2014, Webby et al, Liu et al, 2013, Rahman et al, 2011, Yi et al, 2017). JMJD6 has been implicated in a multitude of biological processes, including embryonic development (Bose et al, 2004, Li et al, 2003, Kunisaki et al, 2004), cell cycle control (Wang et al, 2014a), cellular proliferation and motility (Lee et al, 2012, Chen et al, 2014), adipocyte differentiation (Hu et al, 2015) and development of various types of cancers, such as breast (Poulard et al, 2015, Lee et al, 2012, Aprelikova et al, 2016), lung (Zhang et al, 2013) and colon cancer (Wang et al, 2014a). …”
Section: Introductionmentioning
confidence: 99%